2022
DOI: 10.3390/ijerph19084888
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial and Nutritional Factors of Depression among Type 2 Diabetes Mellitus Patients: A Systematic Review

Abstract: The rising prevalence of depression among Type 2 Diabetes Mellitus (T2DM) patients has triggered an alarming situation, and further actions need to be taken by health care professionals and policymakers to curb the issue. There is a lack of evidence review in terms of the biopsychosocial and nutritional factors that are related to depression among T2DM. Hence, this review aimed to identify available evidence on the biopsychosocial and nutritional factors associated with depression among T2DM patients based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
0
7
0
2
Order By: Relevance
“…Nutritional factors may play an important role in mental health status among T2DM patients [ 67 ]. In this review, two studies reported that vitamin D deficiency was related to mental well-being and poor mental health status, which is depression.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional factors may play an important role in mental health status among T2DM patients [ 67 ]. In this review, two studies reported that vitamin D deficiency was related to mental well-being and poor mental health status, which is depression.…”
Section: Discussionmentioning
confidence: 99%
“…Foi observada evidência de que o IMC e a presença outras doenças crônicas estão relacionadas à ocorrência de depressão em pacientes com diabetes tipo 2 (Amsah;MD Isa;Ahmad, 2022;Felisberto et al 2017;Nguyen et al, 2021) A ocorrência de outras comorbidades e doenças crônicas como hipertensão e doenças cardíacas de um modo geral, foram apontadas com maior incidência de depressão em indivíduos com DM2 (Amsah;…”
Section: Desenvolvimentounclassified
“…Portanto os tratamentos mais intensos não devem ser desconsiderados, mas o médico deve estar atento aos sinais de estresse e sintomas depressivos.OMukherjee;Chaturvedi, 2019;Nguyen et al, 2021). Entretanto, exercícios físicos excessivos e muito intensos podem causar fadiga que aparenta ser preditor de sintomas depressivos, além de ocasionar uma menor adesão a prática de atividades, que pode afetar o controle da diabetes(Amsah;MD Isa;Ahmad, 2022;Mukherjee;Chaturvedi, 2019).…”
unclassified
“…In 1977, George Engel introduced a biopsychosocial model, which offered the theory that illnesses form through a combination of biological factors, for instance, genetic, psychological, and physiological. He purported that psychological factors that promote sickness are rooted in an individual's health beliefs, behavioral patterns, personality traits, and lifestyle (Amsah et al, 2022). [14] He also pointed out that social factors like family connections, socioeconomic status, and social support, when lacking in efficiency, can be responsible for the onset of disease development.…”
Section: Factors That Influence Nutritional Behaviormentioning
confidence: 99%
“…He purported that psychological factors that promote sickness are rooted in an individual's health beliefs, behavioral patterns, personality traits, and lifestyle (Amsah et al, 2022). [14] He also pointed out that social factors like family connections, socioeconomic status, and social support, when lacking in efficiency, can be responsible for the onset of disease development. (Amsah et al, 2022).…”
Section: Factors That Influence Nutritional Behaviormentioning
confidence: 99%